1954
DOI: 10.1103/physrev.96.1711
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lived Radioactive Aluminum 26

Abstract: hydrogen events" were examined under high magnification to determine whether one or more light tracks were also associated. One example of a pair of light tracks, assumed to be electrons, was found (Fig. 1). s'~e++e +y.(2) followed by the direct decay of the neutral pion, as predicted by Dalitz4 and as observed by various authors'' CpĨ t~P rocess (1) is the charge-symmetric analog of the process which was used to explain the pairs in the negative pion beam: s. +~'+e.(3)Since there are approximately as many neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1956
1956
2006
2006

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…This is in general accord with the effects expected from first dredge-up in Red Giant stars (see Dearborn [73]). However, observations on the grains show overproduction of 17 O and much more extensive destruction of 18 O that is far outside the range to be expected for standard RGB or AGB models [71] [74].…”
Section: Circumstellar Dust Grainsmentioning
confidence: 99%
See 3 more Smart Citations
“…This is in general accord with the effects expected from first dredge-up in Red Giant stars (see Dearborn [73]). However, observations on the grains show overproduction of 17 O and much more extensive destruction of 18 O that is far outside the range to be expected for standard RGB or AGB models [71] [74].…”
Section: Circumstellar Dust Grainsmentioning
confidence: 99%
“…It is thus possible to obtain destruction of 18 O with or without significant 26 Al production and substantial 26 Al production with or without 18 O destruction; however, conditions on oxide versus carbide production discussed below place further constraints on which compositions are possible in a given type of grain. 17 Fig. 4).…”
Section: Almentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, 26 Al (τ = 1.05 Myr) was found to have been present in CAIs with a clear correlation of 26 Mg * with 27 Al (Lee, Papanastassiou, & Wasserburg 1976. Early suggestions by Urey (1955) and Urey & Donn (1956) indicated that the nuclide 26 Al, which had just then been discovered (Simanton et al 1954), was the only reasonable source for the heating and melting of planetesimals.…”
Section: Se Non è Vero è Bene Trovato Ancient Italian Motto 1 Introdumentioning
confidence: 99%